(untitled) (KONFERENSIYA, 2025)
This research investigates the cognitive representation and conceptual organisation of formulaic expressions in English, Russian, and Uzbek through a synthesis of usagebased linguistics, cognitive mapping, and corpus analysis. This study employs COCA, the British National Corpus, and the Russian National Corpus, integrating concepts from Construction Grammar, conceptual metaphor theory, and frame semantics to examine the functioning of linguistic units as symbolic form-meaning pairings shaped by frequency, entrenchment, and chunking. The study demonstrates that formulaic expressions encapsulate both universal cognitive mechanisms, including metaphorization, personification, and prototype-based categorisation, as well as culturally specific conceptualisations rooted in the worldview of each community. English terms emphasise human agency and practical problem-solving; Russian expressions highlight perseverance, fatalism, and philosophical reflection; while Uzbek expressions illustrate collectivist principles, agricultural symbolism, and spiritual notions of blessing and reverence. The research illustrates that by correlating linguistic patterns with conceptual domains such as time, effort, fate, social connections, and emotional experience, formulaic language serves as a cognitive tool for structuring cognition and as a cultural artefact that embodies collective social knowledge. The findings advance cross-linguistic cognitive research by demonstrating how corpus-derived data and conceptual mapping techniques can reveal the deep cognitive and cultural foundations of formulaic expressions across multiple languages